Characterization of the flavoenzyme XiaK as an N-hydroxylase and implications in indolosesquiterpene diversification. Issue 7 (22nd May 2017) - Zhang, Qingbo; Li, Huixian; Yu, Lu; Sun, Yu; Zhu, Yiguang; Zhu, Hanning; Zhang, Liping; Li, Shu-Ming; Shen, Yuemao; Tian, Changlin; Li, Ang; Liu, Hung-wen; et al.
Abstract : Flavoenzymes are ubiquitous in biological systems and catalyze a diverse range of chemical transformations. Abstract : Flavoenzymes are ubiquitous in biological systems and catalyze a diverse range of chemical transformations. The flavoenzyme XiaK from the biosynthetic pathway of the indolosesquiterpene xiamycin A is demonstrated to mediate the in vivo biotransformation of xiamycin A into multiple products, including a chlorinated adduct as well as dimers characterized by C–N and N–N linkages that are hypothesized to form via radical-based mechanisms. Isolation and characterization of XiaK in vitro shows that it acts as a flavin-dependent N -hydroxylase that catalyzes the hydroxylation of xiamycin A at the carbazole nitrogen to form N -hydroxyxiamycin, a product which was overlooked in earlier in vivo experiments because its chemical and chromatographic properties are similar to those of oxiamycin. N -Hydroxyxiamycin is shown to be unstable under aerobic conditions, and characterization by electron paramagnetic resonance spectroscopy demonstrates formation of an N -hydroxycarbazole radical adduct. This radical species is proposed to serve as a key intermediate leading to the formation of the multiple xiamycin A adducts. This study suggests that non-enzyme catalyzed reactions may play a greater role in the biosynthesis of natural products than has been previously recognized.